Coaching U6 players with Tom Goodman - Reedswain (firm) ([Spring City, PA.] : Reedswain)
This series of videos coaches the movement education approanh to coaching, simpl activities that focus on balance, movement and comfort with the ball, small sided games and fun, imaginative environment for the little ones
Title from title screen
Instructor/Coacher: Tom Goodman
Keywords: Soccer -- Coaching; Soccer